Regulation of postsynaptic structure and protein localization by the Rho-type guanine nucleotide exchange factor dPix. - Parnas, D.; Haghighi, A.P.; Fetter, R.D.; Kim, S.W.; Goodman, C.S. (Neuron, 2001)
Mutations in dpix were recovered from a large-scale screen in Drosophila for genes that control synaptic structure. dpix encodes dPix, a Rho-type guanine nucleotide exchange factor (RtGEF) homologous to mammalian Pix. Here we show that dPix plays a major role in regulating postsynaptic structure and protein localization at the Drosophila glutamatergic neuromuscular junction. dpix mutations lead to decreased synaptic levels of the PDZ protein Dlg, the cell adhesion molecule Fas II, and the glutamate receptor subunit GluRIIA, and to a complete reduction of the serine/threonine kinase Pak and the subsynaptic reticulum. The electrophysiology of these mutant synapses is nearly normal. Many, but not all, dpix defects are mediated through dPak, a member of the family of Cdc42/Rac1-activated kinases. Thus, a Rho-type GEF and Rho-type effector kinase regulate postsynaptic structure.